Renal-aortic ratio as an objective measure of renal artery diameter a computed tomography angiography study - Majos, Marcin (BMC Cardiovasc Disord, 2019)
BACKGROUND: Considering vital role of renal arteries in many surgical procedures, diameter of renal arteries seems to be an important measure of kidney perfusion. In this study, we analyzed a new parameter, renal-aortic ratio (R-Ar) as an objective measure of the renal artery diameter. METHOD: The study included CT angiographic images from 254 patients (129 women and 125 men). R-Ar was calculated by dividing the diameter of the main renal artery for each kidney by the aortic diameter. RESULTS: R-Ar values for the whole study group ranged between 0.0863 and 0.5083; the ranges of R-Ar values for women and men patients were 0.1150–0.5083 and 0.0863–0.4449, respectively. In 412 cases (81.10%), the kidney was supplied by a single renal artery (RA variant) and in 96 (18.90%) by more than one artery (sRA variant). A significant difference was found in R-Ar values for RA and sRA variants (p = 0.0008). When the anatomical variant of renal perfusion was not considered on statistical analysis, a significant difference was found between the R-Ar values for women and men (p = 0.0259). No statistically significant difference was observed in R-Ar values for the right and left kidneys (p = 0.3123). Spearman’s coefficient of rank correlation between patient age and renal-aortic ratio values for the whole study group equaled − 0.36. CONCLUSION: The analysis of the renal-aortic ratio values demonstrated that the diameter of renal arteries depended primarily on their number, and the relative diameter of renal arteries in women was larger than in men.